The Premedical Student: His Progress: A Study of a Cohort of Premedical Students at the University of British Columbia - Anderson, Donald O. (1965)
Since September 1961, a prospective study of premedical and science students has been conducted at the University of British Columbia. On completion of their sophomore year, after a year of changes from one group to another or withdrawal from either group, only 82 students existed in the diminished Premedical cohort while 137 students existed in the augmented Science cohort. These two groups have now become similar demographically, and their academic potential, as indicated by achievement and ability tests, has also become similar in terms of their mean test scores. In academic performance the present Premedical cohort has displayed some superiority over the Science cohort in high school, freshman and sophomore years. The sophomore premedical mean grade was 66.0% compared with 63.7% for the Science cohort. The hypothesis is developed that these findings reflect a difference in motivation, and therefore that perception of ultimate career goals will motivate and affect academic performance of students in their undergraduate years.